Penetration of renewable sources through solar systems: a case study Kosovo - Blerina Bylykbashi; Bukurije Hoxha (Institute of Advanced Engineering and Science, 2022)
This paper analyzes the potential of solar energy and the efficiency of a solar system for real measurements. During the analysis, one-year radiation measurements for the city of Pristina were used. Analyzes show a high potential for exploitation. What affects the increase of efficiency of such systems is the possibility of use throughout the year. For each respective month is shown the potential of thermal energy that can be achieved and efficiency. The paper highlights the role of solar energy in maximizing the penetration of renewable sources. The analysis shows that in August the coverage of the needs for hot sanitary water from the proposed solar system is 99% and minimally in January by 16%. Taking into account the seasonal changes that apply to the country, I consider that a possible combination of central heating systems with those of sanitary water - solar system would be an adequate solution.